Analysis of the Accuracy of ICD-10 Codes in Outpatient Diagnoses at the Kijang Health Center: Analisis Ketepatan Kode ICD-10 Pada Diagnosis Pasien Rawat Jalan Di Puskesmas Kijang - Putri, Riza Suci Ernaman; Kusumo, Retno; Wulandari, Siti (Universitas Muhammadiyah Sidoarjo, 2025)
Coding accuracy is very important in medical records. This is related to the use of medical records seen from the administrative aspect, medical aspect, legal aspect, financial aspect, research aspect and documentation aspect. Code accuracy produces good medical records that can be used as a source of decision making. The diagnosis code is considered appropriate and accurate if it matches the patient’s condition. The aim of this study was to find out the causal factors and percentage of ICD- 10 code occurrence in the diagnosis of outpatients at the Kijang Public Health Center. The research method used is quantitative descriptif by using independent cross-sectiational bonding. The analysis of the accuracy of codes diagnosed in correct patients was 66.7% or 66 cases and the inaccurate diagnoses were 33.3% or 33 cases. The influencing factors are man, method and material.